2016
DOI: 10.1371/journal.pone.0167844
|View full text |Cite
|
Sign up to set email alerts
|

Sweat Facilitated Amino Acid Losses in Male Athletes during Exercise at 32-34°C

Abstract: Sweat contains amino acids and electrolytes derived from plasma and athletes can lose 1-2L of sweat per hour during exercise. Sweat may also contain contributions of amino acids as well as urea, sodium and potassium from the natural moisturizing factors (NMF) produced in the stratum corneum. In preliminary experiments, one participant was tested on three separate occasions to compare sweat composition with surface water washings from the same area of skin to assess contributions from NMF. Two participants perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 27 publications
2
61
0
Order By: Relevance
“…pyrrolidone carboxylic acid, urocanic acid, serine, histadine, ornithine, glycine, alanine, aspartic acid, lysine) a NA NA Secretory mechanisms are unknown [6]. Present in sweat but varied in concentrations perhaps because of contamination [15] Natural skin moisturizers, maintain barrier integrity of skin [206,207] Skin surface contamination, both of epidermal origin and residual amino acids in the sweat gland lumen [15,136,207] Proteolytic enzymes a NA NA Derived from eccrine sweat gland [10,456] and/ or epidermis [423]. Concentrations increase with increasing sweating rate [457].…”
Section: Overview Of Sweat Compositionmentioning
confidence: 99%
“…pyrrolidone carboxylic acid, urocanic acid, serine, histadine, ornithine, glycine, alanine, aspartic acid, lysine) a NA NA Secretory mechanisms are unknown [6]. Present in sweat but varied in concentrations perhaps because of contamination [15] Natural skin moisturizers, maintain barrier integrity of skin [206,207] Skin surface contamination, both of epidermal origin and residual amino acids in the sweat gland lumen [15,136,207] Proteolytic enzymes a NA NA Derived from eccrine sweat gland [10,456] and/ or epidermis [423]. Concentrations increase with increasing sweating rate [457].…”
Section: Overview Of Sweat Compositionmentioning
confidence: 99%
“…[42][43][44][45][46] -Humans: ammonia, amino acids, small VOCs such as isoprene and lactic acid, unsaturated oils such as squalene, triglycerides, and fatty acids, personal care products such as siloxanes. [29][30][31][47][48][49][50][51] -Microbes: VOCs. 52 -Consumer products: phthalates and many others, including volatile chemical products (VCPs).…”
Section: The Physical Nature Of the Indoor Environmentmentioning
confidence: 99%
“…High levels of exercise activity would increase the requirement for protein intake and for protein turnover in order to offset the increased losses of free amino acids arising from demands for energy metabolism, tissue repair and recovery processes [8, 9] as well as excretory losses via sweating [10, 11]. Similar increased demands for amino acids would be seen during illness and recovery from trauma.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the levels of several key amino acids including serine, glycine, histidine, alanine and ornithine are present in sweat at much higher concentrations than occur in the plasma [10, 11, 14, 15]. It was proposed that these levels of amino acids in sweat, as has been found to be the case with sweat electrolytes [16], could be achieved by a process of leaching of the amino acids from the natural moisturising factor in the stratum corneum of the skin to combine with the quantities excreted in sweat [10, 11, 15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation